2010
DOI: 10.1371/journal.pone.0011022
|View full text |Cite
|
Sign up to set email alerts
|

Evidence That SOX2 Overexpression Is Oncogenic in the Lung

Abstract: BackgroundSOX2 (Sry-box 2) is required to maintain a variety of stem cells, is overexpressed in some solid tumors, and is expressed in epithelial cells of the lung.Methodology/Principal FindingsWe show that SOX2 is overexpressed in human squamous cell lung tumors and some adenocarcinomas. We have generated mouse models in which Sox2 is upregulated in epithelial cells of the lung during development and in the adult. In both cases, overexpression leads to extensive hyperplasia. In the terminal bronchioles, a tra… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

10
162
1
1

Year Published

2011
2011
2019
2019

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 198 publications
(174 citation statements)
references
References 34 publications
10
162
1
1
Order By: Relevance
“…17 Furthermore, McCaughan et al 20 reported SOX2 amplification in none of a series of low-grade bronchial lesions, but in all high-grade lesions, suggesting upregulation during preinvasive disease progression. Consistently, Lu et al 25 showed that conditional homozygous SOX2 overexpression in clara cells induces bronchial epithelial hyperplasia with 50% of cases showing a progression to lung cancer in mice.…”
Section: Role Of Sox2 In Carcinogenesis Of Lung Squamous Cell Carcinomamentioning
confidence: 66%
See 3 more Smart Citations
“…17 Furthermore, McCaughan et al 20 reported SOX2 amplification in none of a series of low-grade bronchial lesions, but in all high-grade lesions, suggesting upregulation during preinvasive disease progression. Consistently, Lu et al 25 showed that conditional homozygous SOX2 overexpression in clara cells induces bronchial epithelial hyperplasia with 50% of cases showing a progression to lung cancer in mice.…”
Section: Role Of Sox2 In Carcinogenesis Of Lung Squamous Cell Carcinomamentioning
confidence: 66%
“…These results support our previous findings, indicating that patients with lung squamous cell carcinomas harboring an embryonic stem cell-like gene expression signature, including SOX2 expression, exhibit significant better survival than patients with tumors lacking this signature. 9 Consistently, Lu et al 25 were able to show in a cohort of early stage lung squamous cell carcinomas that patients with SOX2 expression above the median show prolonged overall survival.…”
Section: Role Of Sox2 In Carcinogenesis Of Lung Squamous Cell Carcinomamentioning
confidence: 67%
See 2 more Smart Citations
“…Sex determining region-Y-related high mobility group box (SOX) 2 is a transcription factor that is involved in the maintenance of embryonic stem cell pluripotency and in multiple developmental processes. It is overexpressed in certain poorly differentiated subtypes of cancer (eg, lung, 24,25 breast, 26,27 and colorectal 28,29 cancers). SOX2 is not only a prognostic indicator in these cancers but also a candidate for cancer stem-like cell/tumor-initiating cell-targeting T-cell-based immunotherapy.…”
mentioning
confidence: 99%